Plenty Of Room For Biology At The Bottom : an Introduction To Bionanotechnology. - Gazit, Ehud (World Scientific, 2007)
Written by a leading nanobiologist actively involved at the forefront of the field both as a researcher and an educator, this book takes the reader from the fundamentals of nanobiology to the most advanced applications. The book is written in such a way as to be accessible to biologists and chemists with no background in nanotechnology. It is reader-friendly and will appeal to a wide audience not only in academia but also in the industry and anyone interested in learning more about nanobiotechnology. The book includes a glossary and a selected list of companies actively involved in nanobiotech.